Understanding Severance Pay - Donald O. Parsons (Institute for the Study of Labor (IZA), 2013)
Severance pay, a fixed-sum payment to workers at job separation, has been the focus of intense policy concern for the last several decades, but much of this concern is unearned. The design of the ideal separation package is outlined and severance pay emerges as a natural component of job displacement insurance packages, serving both as scheduled reemployment wage insurance and, if search moral hazard is a problem, as scheduled UI. Like any firm-financed separation expenditure, severance pay can induce excessive job retention, but such distortions do not appear to be of practical significance at benefit levels typically mandated in the industrialized world. Moreover there is no evidence that firms attempt to avoid these firing cost distortions by substituting severance savings plans, which have zero firing costs. Indeed severance insurance plans similar to those mandated are often offered voluntarily in the U.S. The appropriate role of government in the market for severance pay is briefly considered.
Keywords: J65; J41; J33; J08; 330; severance pay; job displacement; firing costs; unemployment insurance; moral hazard